Celebrates Ramadan with UMP, PERAMAH and community of Pekan - Siti Sarah, Mohamad Rajimi (2017)
Universiti Malaysia Pahang collaborates with Program Mesra Dakwah Club (PERAMAH) to distribute foodstuffs as well as health kit to the community of Kg. Serun Pantai in Nenasi Pekan in a program to celebrate the coming of Ramadan, ‘We Love We Care’ with PERAMAH recently.